Análises térmicas e processo de sinterização da cerâmica KSr2Nb5O15 dopada com CuO - Vieira, Delia do Carmo [UNESP]; Cardoso, Celso Xavier [UNESP]; Duran, Rafael Matos (Sociedade Brasileira de Química, 2009)
KSr2Nb5O15 is a ferroelectric material. The sintering process of the KSr2Nb5O15 ceramic doped with different amounts of CuO was investigated in this research. It was found that CuO is effective as promoter of the densification process of the KSN ceramic. The developed microstructures were different due to the amount of CuO and secondary phases were observed in the microstructures. However, the results of X - ray diffraction showed that only the tetragonal tungsten bronze (TTB) structure was identified in all the investigated ceramic systems. The thermal behavior of CuO and also of the CuO - KSN phase mixture was investigated by thermal analysis.
Thermal analysis and sintering process of KSr2Nb5O15 ceramic doped with CuO
Keywords: TTB niobates; thermal analysis; liquid phase sintering